การผลิตและตรวจสอบสมบัติของฟิล์มจาก Anabaena sp. - สุพิชญา วิริยะหิรัญไพบูลย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
In the present day, utilization of biopolymers including polysaccharide (PS) and polyhydroxybutyrate (PHB) as the substitutions of petroleum-based materials has gained widespread attention, as the level of environmental consciousness increases. However, the bottleneck in commercialization of these polymers is the low production yield. Therefore, the aims of this study were to investigate the productions of PS and PHB of a cyanobacterial isolate cultured in different media, and to analyze the physical properties of films casted from these polymers. Results from morphological study and phylogenetic analysis based on 16S rDNA sequences suggested that this cyanobacterial isolate was closely related to Anabaena siamensis. This cyanobacterium grew faster in bold s basal medium (BBM; 0.45±0.07 g/L) than in BG-11 medium, which lacked sodium nitrate (BG-11₀; 0.21±0.05 g/L). The highest PHB and PS yields were 26.8±3.9 and 48.2±5.8 mg/L, after 21-day cultivation in BBM, which were about 2-fold higher than those of BG-11₀ (14.5±3.5 and 21.0 ± 4.2 mg/L, respectively). The film obtained from solvent casting using PHB (1% w/v) exhibited low transmission of UV. Similarly, the composite film obtained from PSs (0.35% w/v) blended with carboxymethyl cellulose (1.5% w/v) also showed excellent optical properties, which light transmission is one of an important property for packaging applications.